Effect of defatted soybean flour on the flavour of extruded mixtures with wheat flour - J. Pokorný; A. Farouk Mansour; F. Pudil; V. Janda (Czech Journal of Food Sciences, 2002)
Mixtures of wheat semolina, 5% glucose and 0-30% defatted soybean flour were used for the preparation of extruded samples using a pilot plant single screw extruder, maximum temperature being 140°C. The browning reactions were only moderate, the intensities of the trichromatic a* coordinate increased, and some changes were observed in chroma and the odour difference ΔE*. The sensory acceptability improved by increasing the content of soybean flour, the odour intensity increased, and some changes were observed in the sensory profile. Volatile substances were isolated using a SPME procedure, and the volatiles were separated using a Fisons GLC 8000 apparatus equipped with a mass spectrometer. Among the flavour active volatiles, pyrazines were the most prominent class of compounds, especially methyl and ethyl substituted derivatives. Pyrrole and furan substituted pyrazines were found only in small amounts because of the low extrusion temperature. Other furan and pyrrole derivatives had a lesser effect on flavour because of their relatively low amounts. Aldehydes, fatty acids, ketones, and other aliphatic derivatives contributed only a little to the resulting flavour. Compared to the mixtures of semolina and glucose only, the additions of defatted soybean flour moderately increased the number of substituted pyrazines detected in the extruded mixtures but increased substantially the pyrazine fraction in the total peak area. Among furan derivatives, 2-furancarboxaldehyde, 2-furanmethanol and 5-methyl-2-furyl alcohol belonged to the most prominent derivatives. Among other compounds, acetic acid, butyrolactone and maltol should be mentioned.